Analysis of the usefulness of a serious game to raise awareness about mental health problems in a sample of high school and university students: relationship with familiarity and time spent playing video games. - Cangas, Adolfo J.; Navarro-Gómez, Noelia; Aguilar-Parra, José M.; Trigueros, Rubén; Gallego, José; Zárate, Roberto; Gregg, Melanie (MDPI, 2019)
Background: One of the main challenges in the field of mental health today is the stigma towards individuals who have psychological disorders. Aims: This study aims to analyse the usefulness of applying a serious game developed for the purpose of raising awareness among students about mental health problems and analyse whether its usefulness can be influenced by the type of video games or the time that students usually devote to playing with this type of entertainment. Method: The serious game introduces four characters who display the symptoms of different psychological disorders. A total of 530 students participated in the study, 412 of whom comprised the experimental group and 118 the control group, 291 came from secondary school classes and 239 were university students. Results: The findings show that this serious game significantly reduced total stigma among students. Variables like time habitually spent playing video games or video game preference had no bearing on the results. Conclusion: Our findings suggest that the serious game is an appropriated tool to reduce stigma, both in high school and university students, independently of the type of video games that young people usually play, or time spent playing video games.
Keywords: Universidades - Servicios de promoción de la salud; Educación sanitaria; Salud mental - Aspectos sociales; Serious games; Stigma; Mental health; Education; Inclusion